Challenges in expert ratings of marine habitat and species sensitivity to anthropogenic pressures - Niko Kallio; Jesper H. Andersen; Jacob Carstensen; Elena Gissi; Benjamin S. Halpern; Linus Hammar; Ciaran Murray; Vanessa Stelzenmüller; Andy Stock; Samuli Korpinen (Scientific Reports)
Abstract Expert knowledge can help fill gaps in quantitative empirical information about complex ecological phenomena. We examined the level of agreement between 21 studies that collected expert ratings of the sensitivity of species and habitats to human activities and their pressures as input data for mapping the human impact on marine ecosystems. Our analyses revealed broad agreement about which human activities and pressures many species and habitats are sensitive to. These agreements reflect a common view of the main threats to ocean ecosystems. In contrast, scores provided by individual experts varied both within and across studies. Sensitivity scores collected with the same method for different regions were often more similar than scores collected for the same region but with different methods. These results highlight how inconsistencies in the design of many expert surveys can lead to variable outcomes. It is important to employ more consistent and theoretically grounded methods and protocols when eliciting expert ratings of species’ sensitivity to pressures, to ensure compatibility across studies and maintain rigour in analyses supporting effective ocean management.